Effect of prophylactic and therapeutic low molecular weight heparins on mortality in 15, 704 COVID-19 patients. A systematic review and a meta-analysis. (14th October 2021) - Pani, A; Giossi, R; Menichelli, D; Tratta, E; Romandini, A; Roncato, R; Nani, A; Schenardi, P; Diani, E; Fittipaldo, V A; Farcomeni, A; Scaglione, F; et al.
Abstract: Background: Antithrombotic treatment, including low molecular weight heparin (LMWH), has been proposed as a potential therapy for Coronavirus disease 2019 (COVID-19), to counteract diffuse intravascular clotting activation. However, it is unclear whether prophylactic or therapeutic doses are similarly effective in reducing mortality. Methods: We performed a systematic review and meta-analysis of clinical studies to evaluate the efficacy of heparin (either, LMWH or fondaparinux) compared to no anticoagulation in reducing overall mortality. A subgroup analysis comparing prophylactic or therapeutic regimen was performed. Secondary endpoints were major bleeding and length of hospital stay (LOS). Results: 12 studies were included, 2 prospective and 10 retrospective with 15, 704 patients. Of these, 11, 251 (71.6%) were on heparins. Ten studies reported data on all-cause mortality (figure), showing that both prophylactic and full dose reduced mortality (pooled Hazard Ratio [HR] 0.55, 95% confidence interval [CI] 0.48–0.63 and HR 0.49, 95% CI 0.41–0.59, respectively). The prophylactic dose was associated with a lower risk of major bleeding (Odds Ratio [OR] 0.60, 95% CI 0.41–0.87), while a non-significant trend towards an increased risk of bleeding for the therapeutic dose was noted (OR 1.55, 95% CI 0.98–2.43). Finally, LOS was evaluated in 3 studies; the mean difference for prophylactic heparin treatment was −2.38 (−3.14, −1.61) days. Discussion: Heparin is effective in reducing mortality in COVID-19 patients, with therapeutic and prophylactic regimens showing a similar reduction in the mortality rate. Prophylactic dose may be considered as the first choice in all patients with COVID-19 requiring hospital admission. FUNDunding Acknowledgement: Type of funding sources: None.